PENGARUH PENERAPAN JOYFUL LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI BANGUN DATAR KELAS III SDN 001 TERATAK - Bayu Saputra; Fadhilaturrahmi; Zulhendri; Joni; Rusdial Marta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the implementation of the joyful learning strategy on the mathematical problem-solving ability of the third-grade students of SDN 001 Teratak on plane geometry. This study uses a quantitative approach with a pre-experimental design method using a one-group pretest-posttest design. The subjects of the study were the third-grade students of SDN 001 Teratak, consisting of 20 students in the experimental class and 20 students in the control class. Data collection techniques were carried out through mathematical problem-solving ability tests in the form of pretests and posttests as well as observations during the learning process. The research instrument was a validated test item. Data were analyzed using descriptive statistics and inferential statistics with normality tests and independent sample t-tests assisted by SPSS. The results showed that based on the independent sample t-test, the significance value was smaller than 0.05 (Sig. <0.05), so there was a significant difference in conceptual understanding between students who learned using the joyful learning strategy and students who learned with the CTL method. Thus, the use of joyful learning strategies has a significant effect on increasing students' conceptual understanding compared to CTL learning on students' mathematical problem-solving abilities on flat shape material for class III SDN 001 Teratak.